Gibalna aktivnost dializnih bolnikov - Bogataj, Špela (Šport (Ljubljana), 2018)
Nowadays, we are facing a large number of chronical diseases, including chronic kidney disease (CKD). Patients in whom CKD advances to the end stage disease are treated mostly with hemodialysis, which takes place three times a week for four to five hours. Due to the nature of the disease, physical inactivity and diet restrictions, these patients suffer from cardiovascular and infectious disease more than the general population does. Muscular atrophy and physical impairement also develop. Systematic literature review shows that physical activity has many positive effects on the health of dialysis patients. In some dialysis centers around the globe the physical exercise program runs simultaneously with hemodilaysis. Research shows beneficial effects of such training. In Australia, the intradialytic exercise pilot program was even so successful that more than 70% of the patients now participate in such a training program. The advantage of this type of program is also the constant presence of a kinesiologist during the exercise. Many previous studies report the effects of intradialytic training on a customized ergometer, which can currently be considered as the gold standard of the training type for dialysis patients.
Keywords: bolniki; dializa; gibalna aktivnost; kronična ledvična bolezen; raziskave; rehabilitacija; telesna aktivnost